(untitled) (Simbiótica. Revista Eletrônica, 2022)
The narrative fragmentation that characterizes Postmodernity is the birthplace of the epistemological phenomenon of post-truth, in which the objective truthfulness of the information matters less than its alignment with the reader’s ideological pretensions. This scenario, combined with the unprecedented ability of new technologies to convey news, allows for the emergence and quick spread of false content. It is on this issue that this article focuses, analyzing its deleterious effects on the political-electoral processes, which may signal a crisis in the liberal democracy paradigm. On the other hand, there are also limitations to the effectiveness of state regulatory measures. Finally, the feasibility of the concept of digital literacy is discussed as a useful tool for mitigating the problem that does not affect freedom of expression in the discursive sphere. Keywords: fake news; post-truth; digital literacy.